Impression Management and Work Motivation in Improving Employee Performance PT. Enseval Putera Megatrading, Tbk Bandung - Irfan Imamul Haqiqi; Dede Hertina (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
Human resources are one of the most important factors in the company because humans are the driving force for all activities within the company. As humans, employees have thoughts and feelings that affect the course of the company's activities. This study aims to determine the effect of Impression Management and Work Motivation on Employee Performance at PT. Enseval Putera Megatrading, Tbk Bandung. The sample used as many as 100 employees in the company. The method used is descriptive analysis with data collection through interviews, observations, and questionnaires. This study uses a model of factor analysis, reliability analysis, descriptive analysis, classical test analysis, analysis of determination and multiple linear regression analysis. Based on the research results from the questionnaire, it shows that impression management is categorized as good with an average score of 3.64 and work motivation is categorized as good with an average score of 3.66, the results of testing with smart PLS. Impression management and work motivation simultaneously (simultaneously) have a significant effect on employee performance, as evidenced in the F test. H0 is rejected, indicating that the independent variables, namely impression management and work motivation, jointly affect employee performance. and the partial effect shows that impression management and work motivation have an effect on employee performance.